POP-2: In vitro effect of the hexane and dichloromethane fractions of the fresh leaf ethanol extract of Euphorbia tithymaloides L. On the inhibition of the enzymes hyaluronidase, cycloxygenase and lipoxygenase - Castillo Contreras, Osnaider J.; Alba Chávez, Luz M.; Rodelo Vergara, Cindy P.; Márquez Vizcano, Rita L. (Revista Productos Naturales, 2022)
Euphorbia tithymaloides is a plant of therapeutic interest thanks to the healing properties described by the communities that traditionally use it as an anti-inflammatory. Consequently, the in vitro inhibitory effect of the hexane and dichloromethane fractions of the fresh leaf ethanol extract
Keywords: Inflammation; anti-inflammatory; phytochemistry; natural products